2021
DOI: 10.35808/ersj/2672
|View full text |Cite
|
Sign up to set email alerts
|

Smart Island and Sustainable Tourist Development with the Example of Madeira. Part 2: Analysis of Expectations of Local Community and Tourists

Abstract: Purpose:The main objective of the analysis was to investigate the attitudes of the local community towards tourists and tourism in Madeira, and their opinions on sustainability, smart city concept and the impact of tourism on the island. The survey also explored the expectations of both groups towards further development of tourism on the island and sought suggestions for solutions and opportunities for sustainable tourism development. Design/Methodology/Approach: The research presented in this paper was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…This behavior fits into the concept of a "conscious" tourist, which was described by, among others, Priveli (2023). Every fourth respondent indicated that they very often choose local restaurants instead of well-known "chain" restaurants, which was confirmed by the research of Majdak et al (2021). It is worth emphasizing that almost 9 out of 10 respondents never leave garbage behind on the beach or in the forest.…”
Section: Environmentally and Socially Sustainable Behavior Of Generat...mentioning
confidence: 52%
See 1 more Smart Citation
“…This behavior fits into the concept of a "conscious" tourist, which was described by, among others, Priveli (2023). Every fourth respondent indicated that they very often choose local restaurants instead of well-known "chain" restaurants, which was confirmed by the research of Majdak et al (2021). It is worth emphasizing that almost 9 out of 10 respondents never leave garbage behind on the beach or in the forest.…”
Section: Environmentally and Socially Sustainable Behavior Of Generat...mentioning
confidence: 52%
“…Quite high they rated acquiring knowledge about the places visited. Likewise, research by Majdak et al (2021) shows that for the sustainable development of tourism, it is important for tourists to have knowledge about the tourist reception area, its products and customs.…”
Section: Environmentally and Socially Responsible Behavior During Tou...mentioning
confidence: 99%
“…Moreover, the phenomenon of overtourism may also appear in a situation where the thresholds of tourist absorption or capacity are not exceeded, but a reduction in the level of quality of life and the value of tourist experiences can be observed among both residents and visitors (Majdak et al, 2021a;2021b).…”
Section: Overtourism and Sustainable Management: Theoretical Contextmentioning
confidence: 99%
“…Więcej informacji o badaniach i uzyskanych wynikach zawarto w publikacjach(Majdak et al 2021a;Majdak et al 2021b). …”
unclassified
“…More information about research and obtained results are available in the following publications(Majdak et al 2021a;Majdak et al 2021b). …”
mentioning
confidence: 99%